The Impact of Resin as a Substitute for Cement (Polymer) and Ceramic as a Substitution of Fine Aggregate in High-Quality Concrete - Griff Greucenzky; Agung Sumarno; Syafwandi; Agyanata Munthe (Journal of World Conference (JWC), 2022)
Infrastructure is the entire structure and basic facilities needed by the community to support various community activities in daily life. The infrastructure consists of technical facilities, physical, systems, hardware, and software needed to provide services to the community and support the network structure so that the economic and social growth of the community can run well. Concrete is a material that is formed from mining products, therefore concrete has an impact on the environment. The research method used is an experiment using SNI 7656;2012 as a reference. This test was carried out by making 27 concrete samples measuring 15 x 30 cm, 9 samples of polymer concrete with 15% ceramic variation, 9 polymer concrete with 17% ceramic variation, and 9 conventional concrete as comparisons. Polymer concrete has a compressive strength of 31.53 MPa for the 15% ceramic variation and has the highest compressive strength of 32.22 MPa for the 17% variation. The compressive strength of polymer concrete with a variation of 15% is 5.69% stronger than normal concrete, while polymer concrete with a variation 17% is 11.36% higher than normal concrete.